Pandangan Hukum Islam Terhadap Penggunaan Media Sosial di Era Modern : (Akhlak dalam Bermedia Sosial) - Renny Novita; Muannif Ridwan; Ade Suria Putra; Adimar (Jurnal Indragiri Penelitian Multidisiplin, 2022)
In this era of globalization and modernization, technology is growing rapidly and in every country inevitably follows the times and technology. Because if it is not followed, Indonesia will be left behind and become an undeveloped country. However, there are several things that affect the lives and views of today's society, especially Muslims at this time, namely social media. If in the age of social media using television, radio, newspapers, in the current era of globalization, social media has sprung up a lot like the internet and this has many impacts, both positive and negative impacts from all kinds of social media that already exist and are developing at this time. . As Muslims, we should know all the ins and outs and the rules so that they are in accordance with Islamic law. It is said so because there are many things in social media that are irrelevant and damage the order of life that is in accordance with the law. There are too many things that deviate from religious teachings and norms that have been applied, therefore as social media users should be able to do all kinds of uncertain things that already exist in social media today so that they are dragged and captivated by all the relationships that exist in the media. social it self.